A new model for acoustic attenuation of GHz waveguide induced by metal electrodes in piezoelectric composites. (1st October 2022) - Zhu, Feng; Qu, Yilin; Pan, Ernian
Highlights: A new model based on electromagnetic (or optic) property of metal is established. 3D dispersion curves with energy dissipation are investigated by a novel root-searching method. A rapid conversion phenomenon in wave mode shapes is identified. Two new features which significantly change the acoustic attenuation are observed. Besides the electromagnetic property, mechanical property of electrode also impacts the attenuation in GHz. Abstract: Acoustic attenuation in piezoelectric composites is an important factor and it can be induced by various sources, including viscoelasticity and semi-conductivity. Since the radio frequency of fifth generation (5G) mobile communication technology has achieved at GHz, the attenuation of the piezoelectric acoustic devices operating at GHz frequency must be addressed. Unfortunately, when frequency is high, the electrode cannot be treated as an electric resistance that follows the traditional Ohm's law. Therefore, in this paper, the acoustic attenuation induced by electrodes, which has been seldom studied in the past, is investigated. A novel multi-disciplinary model is presented which combines the piezoelectric theory and the electromagnetic (or optic) property of metal, instead of the zero-thickness surface electrode model and Ohm's law with a fixed conductivity. Based on this model, the dispersion equations for the composite structure are derived in the case of elastic metal electrode with realistic optical properties, as compared with the ideal short circuit boundary condition case. Three-dimensional (3D) dispersion curves of these two cases are further calculated by two forms of the novel root-searching method introduced recently, accompanying with the wave mode shapes on certain branches. Based on these results, two important features of the wave motion, which significantly change GHz acoustic attenuations, are identified, with their underlying mechanisms. These new features could provide a reference in safe and better design of piezoelectric acoustic devices. Graphical abstract: Image, graphical abstract